Impacts of barrage flushing and flooding in operations on upstream total suspended solids - Law, P.L; Law, I.N.; Lau, H.H; Kho, F. W. L. (Springer Science, 2007)
This study looks into the impacts of Sarawak Barrage (located in Kuching City, State of Sarawak, Malaysia) flushing and flooding-in operations on upstream total suspended solids (TSS). Water samples were collected from three upstream stations on 17th, 18th and 19th of August 2000. During flushing, it was observed that TSS levels increased over a distance of 11 km upstream. Maximum TSS recorded 250 mg/L at 1.5 km, 120 mg/L at 6 km, and 85 mg/L at 11 km upstream. During flushing, TSS levels increased with depth, and upstream turbulence intensities were indirectly proportional to distance from barrage. During flooding-in operation, TSS decreased from 249 to 155 mg/L at 1.5 km near the bottom, while surface TSS decreased from 86 to 58 mg/L. Generally, during flooding-in operation, TSS increased from 90 to 116 mg/L between 6 and 11 km. During flooding-in operation, maximum bottom TSS recorded 216 mg/L at 6 km upstream. Differences between bottom and mid-depth TSS levels were relatively minimal ranging from 19 to 45 mg/L, whilst the maximum difference between mid-depth and surface TSS was as high as 78 mg/L. After 9 hours of gate closure, a well-mixed regime prevailed from 6 to 11 km upstream with TSS ranged from 35 to 47 mg/L at all the monitoring points regardless of depths.